Evaluation of aircraft wing-tip vortex using PIV - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf Ali (2009)
The formation and development of a wing-tip vortex in a near and extended near filed were studied experimentally. Particle image velocimetry was used in a wind tunnel to measure the tip vortex velocity field and hence investigate the flow structure in a wake of aircraft half-wing model. The purpose of this investigation is to evaluate the main features of the lift generated vortices in order to find ways to alleviate hazardous wake vortex encounters for follower airplanes during start and approach such that the increase in airport capacity can be achieved. First the wake structure at successive downstream planes crosswise to the axis of the wake vortices was investigated by measuring parameters such as core radius, maximum tangential velocities, vorticities and circulation distributions. The effect of different angles of attack setting on vortex parameters was examined at one downstream location. In very early stages the vortex sheet evolution makes the tip vortex to move inward and to the suction side of the wing. While the core radius and circulation distributions hardly vary with the downstream distance, noticeable differences for the same vortex parameters at different angles of attack settings were observed. The center of the wing tip vortices scatter in a circle of radius nearly equal to 1% of the mean wing chord and wandering amplitudes shows no direct dependence on the vortex strength but linearly increase with the downstream distance